Coexistence of both Brenner tumor and cystadenofibroma of ovary in a postmenopausal woman: a rare case - Kalpana, B.; Panda, Soumya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Brenner tumor, and cystadeno fibroma of ovary are rare varieties of ovarian tumor, characterized by presence of solid components. There are very rare instances where both Brenner tumor and cystadenofibroma coexist in a single patient. A 48-year P1L1, postmenopusal woman presented at Guru hospital, Madurai, with chief complaints of on and off postmenopausal bleeding for 6 months. On ultrasonography there were two simple cysts of ovary measuring 6x 6 cm on left side and 4x4 cm on right side. She was managed with total laparoscopic hysterectomy and bilateral salpingoophorectomy. Intraoperatively there was a right ovarian mass of 6x6 cm size and a left ovarian mass of 4x4 cm size. Left ovarian mass reported as benign cystadenofibroma while the right ovarian mass was reported to be brenners tumor on histopathology. As the preoperative imaging are not completely relied for diagnosing these tumors, awareness of the surgeons of these entities is particularly important. The prognosis of both of these tumors is excellent with suitable treatment. They have a very low recurrence risk on compete removal through surgery.